The Effect of Purgative Manna and Clofibrate on Neonatal Unconjugated Hyperbilirubinemia - Abolfazl Mahyar (Acta Medica Iranica, 2019)
This study was conducted to determine the effect of purgative Manna and clofibrate on unconjugated hyperbilirubinemia of term neonates. In this randomized clinical trial study, sixty neonates suffering from unconjugated hyperbilirubinemia were evaluated. The neonates were divided into three groups using balanced block randomization. Group A (control group-received only phototherapy), group B (intervention group-received purgative Manna and phototherapy) and group C (intervention group-received clofibrate and phototherapy). After the intervention, the amount of serum bilirubin reduction was compared between groups. There was no significant difference among group A, B, and C in terms of serum bilirubin reduction in 24, 48 and 72 hours after starting the intervention (P>0.05). The hospital stays in the control group was significantly longer than the intervention groups (P<0.05). No side effects were observed related to using purgative Mienna and clofibrate. The present study showed that prescribing of purgative Manna and clofibrate has no effect on reduction of serum bilirubin level in term neonates with unconjugated hyperbilirubinemia. Thus, it seems that the administration of these drugs is not necessary. Further studies in this regard are recommended.